Boron nanosheets loaded with MoS2 porous sponges for water purification. (June 2021) - Yin, Jiacheng; You, Xu; Zhang, Zexian; Guo, Zhenzhen; Wang, Junshi; Wang, Xianbao
Graphical abstract: Highlights: Boron nanosheets were introduced into photothermal systems to produce clean water. KBMS show good thermal insulation, rapid water evaporation and excellent salt resistance. A water production rate of 1.538 kg m −2 h -1 and photothermal efficiency of 96.5 % were achieved. Abstract: Utilizing solar steam generation to treat seawater and sewage, as an emerging and effective technology, can obtain clean water. There is an abundance of water demand and a shortage of water supply in the world today. Herein, we demonstrate an integrated evaporator of boron nanosheets modified with molybdenum disulfide (MoS2 ) as a photothermal materials and a konjac glucomannan (KGM) sponge with excellent pore structure as a thermal insulator and water supplier for solar clean water generation. A rapid evaporation rate (1.538 kg m −2 h -1 ) and high solar evaporation efficiency (96.5 %) under 1-sun radiation (1 kW m −2 ) can be achieved in the two-dimensional structure system. This work provides a new way to design and manufacture renewable solar steam generation for water purification.